ANALISIS MINAT BELAJAR SISWA PADA PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH - Dina Cantika Novia Ramadani; Nafilah Alimatur Rosyidiyah; Denada Putri; Nur Laili Dina Hafni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to review and synthesize existing literature on students' learning interest in thematic learning at Madrasah Ibtidaiyah (Islamic Elementary School). Learning interest is a key internal factor that drives students' active participation, enthusiasm, and learning outcomes, particularly in thematic learning, which integrates several subjects around one meaningful theme as mandated by the 2013 Curriculum. This research used a literature review method by collecting, analyzing, and synthesizing findings from national journal articles, conference proceedings, and institutional data published between 2016 and 2026. The review shows that students' learning interest in thematic learning at the elementary level is generally influenced by two categories of factors: internal factors, including intelligence, attention, talent, motivation, readiness, and fatigue; and external factors, including teaching methods, learning media, family support, school environment, and teacher-student interaction. Teaching methods and the teacher's approach were consistently identified as the most dominant factor across the reviewed studies, followed by the availability and variation of learning media. Studies conducted specifically in Madrasah Ibtidaiyah found that portfolio-based learning, interactive digital media, and contextual, religiously-integrated themes were effective in increasing engagement. This review concludes that optimizing learning interest in thematic learning requires collaborative efforts among teachers, schools, and families.